Photodegradation and Photoelectrodegradation of Methyl Orange and Methyl Violet Dyes using Graphite/PbTiO3 Composite under Visible Light Irradiation (Universitas Jenderal Soedirman, 2023)
The composite of Graphite/PbTiO3 has been synthesized for photocatalyst and photo-electrocatalyst of Methyl Orange (MO) and Methyl Violet (MV) degradation using a visible light source. The aims of the research were to study the influence of pH of the solution, iradiation time and kinetics study of MO and MV photodegradation, voltage of photoelectrodegradation of MO and MV. Composite of Graphite/PbTiO3 was synthesized by the sol-gel process with Titanium Tetraisopropoxide (TTIP) solution and Pb(NO3)2 powder as the precursors. Graphite/PbTiO3 composite was characterized using X-ray difractometer and FTIR spectrometer. The diffractogram of Graphite/PbTiO3 composite showed peaks at 2θ = 26.507o as a characteristic diffraction of Graphite, and at 2θ = 31.838o and 39.294o as those of PbTiO3. FTIR spectrum of Graphite/PbTiO3 composite exhibits vibration peaks of TiO2 at 609.5 – 420.5 cm-1 and those of Pb-O at 1337.66 cm-1 until 1395.56 cm-1. The photodegradation results showed that Graphite/PbTiO3 composite can degrade MO and MV optimally at a pH = 3. The photodegradation levels of MO and MV were 90.33% and 88.26% for 30 min of visible light radiation, respectively. The photodegradation of MO and MV were following the first-order reaction with a reaction rate constant of 0.4445 min-1 and 0.4244 min-1, respectively. Meanwhile, the photoelectrodegradation of MO was 96.50% at 10 volts and at pH 11, while the photoelectrodegradation of MV was 95.14% at 10 volts and at pH 7. When compared previous research, this result also shows excellent degradation MO and MV using Graphite/PbTiO3 under visible light irradiation. So that the use of visible lights provides an advantage over the use of UV light.